Low IgA Associated With Oropharyngeal Microbiota Changes and Lung Disease in Primary Antibody Deficiency - Berbers, Roos-Marijn; Mohamed Hoesein, Firdaus A. A.; Ellerbroek, Pauline M.; van Montfrans, Joris M.; Dalm, Virgil A. S. H.; van Hagen, P. Martin; Paganelli, Fernanda L.; Viveen, Marco C.; Rogers, Malbert R. C.; de Jong, Pim A.; Uh, Hae-Won; Willems, Rob J. L.; et al. (Frontiers in Immunology, 2020)
Common Variable Immunodeficiency (CVID) and X-linked agammaglobulinemia (XLA) are primary antibody deficiencies characterised by hypogammaglobulinemia and recurrent infections, which can lead to structural airway disease (AD) and interstitial lung disease (ILD). We investigated associations between serum IgA, oropharyngeal microbiota composition and severity of lung disease in these patients. In this cross-sectional multicentre study we analysed oropharyngeal microbiota composition of 86 CVID patients, 12 XLA patients and 49 healthy controls (HC) using next-generation sequencing of the 16S rRNA gene. qPCR was used to estimate bacterial load. IgA was measured in serum. High resolution CT scans were scored for severity of AD and ILD. Oropharyngeal bacterial load was increased in CVID patients with low IgA (p=0.013) and XLA (p=0.029) compared to HC. IgA status was associated with distinct beta (between-sample) diversity (p=0.039), enrichment of (Allo)prevotella, and more severe radiographic lung disease (p=0.003), independently of recent antibiotic use. AD scores were positively associated with Prevotella, Alloprevotella, and Selenomonas, and ILD scores with Streptococcus and negatively with Rothia. In clinically stable patients with CVID and XLA, radiographic lung disease was associated with IgA deficiency and expansion of distinct oropharyngeal bacterial taxa. Our findings highlight IgA as a potential driver of upper respiratory tract microbiota homeostasis.